Ibn Khaldun`s Mixed Learning Concepts Shaping Learning Outcomes and New Concepts of Observational Learning: (Study in Haji Ya’qub Islamic Boarding School Lirboyo Kediri) - Muhammad Farid Asysyauqi; Ali Riyadi; Moh. Irmawan Jauhari (Taskuliah Edukasi Indonesia, 2025)
Ibn Khaldun as a Muslim-Philosopher devetod a lot of learning theories including Behaviorist-Cognitve Social ideas integrally. The dimension of ‘aql tajrībī will be more competent with wāzi’ or the equivalent meaning whose dimension is S-R contingency so that it becomes tajribah-ṣaḥīḥah. At the Haji Ya’qub Islamic Boarding School (PPHY) Lirboyo represents the prototype of the mixed concept which is the reason for this research wan to explore the implementation dan learning outcomes of the mixed concept in PPHY. This qualitative instrumental single case study seeks to explore this with a mature concept and field data obtaainde by observation, interviews and documentation so that the analysis of the OMA system becomes the end of the export tool and even new findings are displayed. This study shows that habituation of the affective basis of the dominan commitment level is formed with stimulus tikrār accompanied by a comparable response. On Average, Informaants experience 3 tikrār both in punistment, instruction of pondok activities such as istigastah, compulsory learning, compulsory lesrning , and skill maturity stage. The ikrāh aspect of the pondok as wāzi’ creates a hierarchical flow of observational learning and skills in contrast to the concept of Bandura where the motiviasional aspect becomes a hierarchical stratification preceding the retention stage